Designing an Islamic Blue Economy Based Salt Sector Development Strategy - Afandi, Muhammad Zainur Rahman; Fahrurrozi, Fahrurrozi; Muhtadi, Ridan (MALIA: Jurnal Ekonomi Islam, 2025)
Introduction: Salt produced using seawater is one of the topics discussed in the concept of blue economy. Blue economy refers to sustainable management in the maritime sector. Blue economy is in line with the Islamic economic system in its application because it is not only profit-oriented but also prioritises environmental sustainability for sustainable economic activities. This article discusses salt management in one of the regions in Madura known as Kampung Garam. The purpose of this study is to provide a deeper understanding of the blue economy in the salt sector from an Islamic economic perspective in Kampung Garam. Methods: This study used a qualitative descriptive method by conducting direct observation, interviews, and documentation with salt farmers and land managers. Results: The results of the study indicate that management in Kampung Garam has begun to meet four blue economy indicators, namely efficient use of natural resources, zero waste, social awareness, and diverse income streams. Conclusion and suggestion: However, salt management in Kampung Garam can still be improved to have a more significant impact on the community in Kampung Garam.